1978
DOI: 10.1103/physrevb.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Erergy loss of correlated charges in an electron gas

Abstract: The energy loss of a pair of charges in correlated motion through an electron gas is calculated using Lindhard's dielectric function, The results of numerical integrations are presented and in particular the cases of low and high velocities are described. Analytical expressions for the energy loss are given for the case of high velocities, which are in excellent agreement with the numerical results. A clear relationship between the energy loss of fast correlated charges and the partition rule for the stopping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
79
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(80 citation statements)
references
References 14 publications
1
79
0
Order By: Relevance
“…Since the pioneering article of Brandt et al [4], who studied the stopping power of swift molecules in solids, a lot of theoretical work has been developed [5]- [13]. Experiments have been mainly done with hydrogen-molecular ions, H + n , ranging from small [14]- [18] to intermediate [19] values of n.…”
mentioning
confidence: 99%
“…Since the pioneering article of Brandt et al [4], who studied the stopping power of swift molecules in solids, a lot of theoretical work has been developed [5]- [13]. Experiments have been mainly done with hydrogen-molecular ions, H + n , ranging from small [14]- [18] to intermediate [19] values of n.…”
mentioning
confidence: 99%
“…(13) and Eq. (4) for large impact parameters, thus reinforcing the validity of our proposed general formula (11). It should be stressed that the sudden approximation, which was used in ref.…”
Section: Modelmentioning
confidence: 99%
“…However, that model is limited to the very beginning of the interaction between the cluster and the target, therefore, it cannot be used to understand several channeling key effects, for instance, the Coulomb heating effect. An important theoretical treatment is the dielectric formalism in a homogenous electron-gas target [2,11] (a detailed review about vicinage effect and dielectric formalism for clusters can be found in ref. [12]) and, to account for the target-core effect, the LDA model (used for clusters in ref.…”
Section: Introductionmentioning
confidence: 99%
“…We calculate the stopping power ratio for the projectile within the framework of the dielectric formalism, which supposes a linear response of the medium to an external perturbation. In this scheme, the instantaneous stopping power ratio for n correlated atomic ions that travel with velocity v in a target is given by [19] …”
Section: Modelmentioning
confidence: 99%
“…The purpose of this paper is to analyse the influence of the geometrical structure of individual boron molecules on the vicinage effects that affect the stopping power, for B + n (n = 2-6). For the range of projectile energies that we will consider (several hundreds of keV per atom), the nuclear energy loss is negligible compared to the electronic energy loss of the molecular ion, which will be calculated using a model based on the dielectric formalism [19]. The energy lost by the components of the molecular ions after they exit from the foil is obtained as an average of the instantaneous energy loss over the dwell time; in this manner we take into account the time variation of the relative distance between the atomic ions dissociated from the molecular ion, as a result of the Coulomb explosion.…”
Section: Introductionmentioning
confidence: 99%